Organizational Communication Strategy In Improving Production Team Performance (Study on the Rafa Television Community of UIN Raden Fatah Palembang) - Martha Triani; Eraskaita Ginting; Gita Astrid (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research is entitled "Organizational Communication Strategies in Improving Production Team Performance (Case Study on the Rafa Television Community of UIN Raden Fatah Palembang)" which aims to analyze how organizational communication strategies are applied in improving the performance of the production team and what are the organizational communication obstacles in improving the performance of the production team. The focus of the research is directed at internal, external, formal, and informal communication strategies carried out by the management and members of the Rafa Television Community. The theory used is Elton Mayo's theory of human relations which emphasizes that the success of an organization depends on satisfaction, motivation, and interaction between members. The research method used is descriptive qualitative with data collection techniques in the form of in-depth interviews, observations, and documentation. Data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the organizational communication strategy in the Rafa Television Community is carried out through several steps, including regular meetings, clear division of jobdesks, production briefings, the use of digital media (WhatsApp, Google Meet), and informal communication outside production hours. These strategies are able to improve coordination, strengthen a sense of community, and motivate team members. However, this study also found obstacles in the form of limited human resources, miscommunication between members, and tight production schedules that have the potential to reduce communication effectiveness. The conclusion of this study is that consistent, adaptive, and participatory organizational communication strategies have been proven to be able to improve the performance of the production team, both in terms of output quality, timeliness, and cooperation between members. Thus, organizational communication not only serves as a means of conveying information, but also becomes an important factor in creating a collaborative and professional work culture in the campus broadcasting community.